Analysis of Visual Evaluation Method and Development of a Digital Inspection Model for State-Owned Building Condition Assessment - Nurhakim, Habibie Budi; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
The condition assessment of State-Owned Buildings (BGN) by the Banjarmasin City DPUPR currently relies on a manual, paper-based system suffering from two fundamental weaknesses: methodological errors in weighting based on Cost Budget Plans (RAB) and process inefficiencies due to manual handling. This applied research aims to (1) identify essential building components using the Cut-Off Point (COP) method, (2) determine objective importance weights using the Analytic Hierarchy Process (AHP), and (3) design a functional digital inspection prototype. The study employs an exploratory sequential design. Results indicate that the Structural Component is the most critical criterion with a weight of 48.16%. Field validation demonstrated that the developed digital prototype is 15.38% more time-efficient and yields a more valid damage score (69.51%) compared to the manual system (60.19%), significantly altering the rehabilitation recommendation. This new model provides a more objective and accurate basis for asset management decision-making.